2023
DOI: 10.3390/metabo13030401
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome × Microbiome Changes Associated with a Diet-Induced Reduction in Hepatic Fat among Adolescent Boys

Abstract: Dietary sugar reduction is one therapeutic strategy for improving nonalcoholic fatty liver disease (NAFLD), and the underlying mechanisms for this effect warrant further investigation. Here, we employed metabolomics and metagenomics to examine systemic biological adaptations associated with dietary sugar restriction and (subsequent) hepatic fat reductions in youth with NAFLD. Data/samples were from a randomized controlled trial in adolescent boys (11–16 years, mean ± SD: 13.0 ± 1.9 years) with biopsy-proven NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Hepatic DNL was significantly decreased in the treatment group (from 34.6% to 24.1%) versus the control group (33.9% to 34.6%) (adjusted week eight mean difference: −10.6% (95% CI: −19.1%, −2.0%)) and body weight decreased slightly (from 91.1 to 89.7 kg) in the treatment group [24]. Furthermore, our previous metabolomics and metagenomics analysis revealed differential changes in the microbiome and metabolome, including amino acid and lipid species associated with the diet treatment and improvement in hepatic steatosis [25].…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Hepatic DNL was significantly decreased in the treatment group (from 34.6% to 24.1%) versus the control group (33.9% to 34.6%) (adjusted week eight mean difference: −10.6% (95% CI: −19.1%, −2.0%)) and body weight decreased slightly (from 91.1 to 89.7 kg) in the treatment group [24]. Furthermore, our previous metabolomics and metagenomics analysis revealed differential changes in the microbiome and metabolome, including amino acid and lipid species associated with the diet treatment and improvement in hepatic steatosis [25].…”
Section: Resultsmentioning
confidence: 66%
“…Intervention, N = 20 1 Control, N = 20 In subsequent studies of data/samples from this parent trial, we reported the effects of the 8-week dietary treatment on hepatic DNL measured using a metabolic labeling protocol with heavy water [24] and on metabolomics and metagenomics profiles [25]. For the present study, which was designed as a follow-up study to build on these previous analyses, high-resolution lipidomics (both untargeted and targeted) were performed on stored plasma samples to assess the differential lipidome changes that occurred with the LFSD treatment.…”
Section: Characteristicmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses revealed that the low free sugar diet, compared to the usual diet, was associated with metabolome and microbiome changes that may reflect biological mechanisms linking dietary sugar restriction to a therapeutic decrease in hepatic fat. 132 …”
Section: Hope For the Future: The Benefits Of Sugar Reduction For Nafldmentioning
confidence: 99%